Application of Dengue Hemorrhagic Fever Information System (SI-DBD) for Recording and Reporting of DHF Suspects at Kota Public Health Centers in Bantaeng Regency - Irsal,; Maria, Ida Leida; Arsin, A. Arsunan; Zulkifli, Andi; Palutturi, Sukri; Amqam, Hasnawati; Basarang, Mujahidah (International Journal of Statistics in Medical Research, 2023)
Background: Dengue fever is the most common viral infection transmitted by Aedes mosquitoes. This disease puts more than 3.9 billion people from 129 countries at risk of contracting dengue fever and causes 40,000 deaths each year. This study aims to analyze the effectiveness of SI-DBD applications for finding, recording, and reporting suspected cases of dengue. Methods: This type of research is a quasi-experiment with The Nonrandomized Control Group Pretest Posttest Design, namely there were two treatment groups (SI-DBD application users) at RT 02 and (a control group) at RT. 01, with a sample of 112 households (1:1 ratio). Data was collected through interviews and reports of suspected dengue fever. Results: There was an increase in reporting of suspected dengue after using the Application of the Dengue Hemorrhagic Fever Information System (SI-DBD) (233.33%). Statistical test results in the intervention group's simplicity, acceptability, data quality, and timeliness had p < 0.000, meaning that there were significant differences in all variables studied in the reporting system using the SI-DBD application. In the control group, statistical tests showed that the acceptability variable had a p < 0.0001, meaning that there were significant differences in the acceptability variable in the use of the manual system before and during the study while the variables were for simplicity, data quality, and timeliness had a p > 0.1797, 0.0833, 0.5567 means that there is no significant difference in these variables in the manual reporting system. Conclusion: SI-DBD application is effective for recording and reporting suspected dengue.